Workplace incivility to predict employee silence: Mediating and moderating roles of job embeddedness and power distance - Deni Gustiawan; Noermijati; Siti Aisjah; Nur Khusniyah Indrawati (Cogent Business & Management, 2023)
The purpose of this study is to investigate whether workplace incivility explains the phenomenon of employee silence behavior in the hospitality sector and how job embeddedness and power distance mediate and moderate this relationship. Data were collected from 359 frontline staff at several hotels and restaurants in Jakarta, Indonesia. The data were analyzed using moderating mediation procedures using the Macro Process. Workplace incivility was negatively related to job embeddedness and positively to employee silence behavior. Job embeddedness was positively associated with employee silence and mediates the relationship between workplace incivility and employee silence. Finally, power distance is directly related to employee silence and moderates the relationship between workplace incivility and employee silence. Hence, the relationship between workplace incivility and employee silence was stronger among employees who perceived higher power distance. The results of this study could be used to guide the management of the hospitality industry. In particular, disrespectful treatment from seniors or supervisors perceived by employees triggers a decrease in job embeddedness and increases silent behavior. Management needs to implement several policies to prevent uncivil actions in the workplace. Moreover, the present study suggests that organizational managers applied special incentives for employees to actively share their information, ideas, and opinions to stimulate employee voice.
Keywords: 650; hospitality industry; job embeddedness; power distance; workplace incivility